2019
DOI: 10.1159/000503918
|View full text |Cite
|
Sign up to set email alerts
|

Ultrafiltration Rate Effects Declines in Residual Kidney Function in Hemodialysis Patients

Abstract: Background: High ultrafiltration rate (UFR) has been associated with increased mortality in hemodialysis (HD) patients. However, the impact of UFR on decline of residual kidney function (RKF) has not been elucidated among patients receiving conventional HD. Methods: We performed a retrospective cohort study of 7,753 patients who initiated conventional HD from 2007 to 2011 and survived the first year of dialysis with baseline UFR and renal urea clearance (KRU) data at baseline and 1 year (5th patient-quarter). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
19
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 25 publications
0
19
0
1
Order By: Relevance
“…Previous studies have reported the association between higher UFR and poor outcomes such as an increased risk of mortality and rapid decline in residual kidney function [5,10,11,13,14]. However, they had the limitation that the objective extracellular volume status was not considered in their analyses.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have reported the association between higher UFR and poor outcomes such as an increased risk of mortality and rapid decline in residual kidney function [5,10,11,13,14]. However, they had the limitation that the objective extracellular volume status was not considered in their analyses.…”
Section: Discussionmentioning
confidence: 99%
“…Various risk factors for worse survival rates have been reported [3][4][5][6][7][8][9]. High ultrafiltration rate (UFR), that is, rapid fluid removal, is recognized as one of the risk factors responsible for these poor outcomes [10][11][12][13][14]. High UFR could increase the development of intradialytic hypotension (IDH), which might be associated with end-organ ischemia of the heart, brain, DOI: 10.1159/000509350 and gut, and this may consequently lead to increased mortality risk [15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…The continual decline in RKF over several HD sessions necessitates an increase in ultrafiltration to account for increased interdialytic weight gain. Nevertheless, higher ultrafiltration rate was associated with a faster decline in RKF among conventional HD dialysis patients [20]. In addition, intradialytic hypotension during HD was negatively associated with RKF after HD initiation [9].…”
Section: Discussionmentioning
confidence: 99%
“…Both of these complications might impair renal recovery. For instance, studies in patients with end-stage renal disease and incident hemodialysis suggest that higher ultrafiltration rates are associated with a decline in residual kidney function [14]. Small observational studies in critically ill patients also suggest that higher UF NET rates are associated with dependence on RRT [15, 16].…”
Section: Introductionmentioning
confidence: 99%